2010
DOI: 10.1111/j.1365-2966.2010.17600.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino heating near hyper-accreting black holes

Abstract: Hyper-accretion discs around black holes emit copious neutrinos and anti-neutrinos. A fraction of the emitted neutrinos convert to electron-positron plasma above the disc through the annihilation reaction $\nu\bar\nu\to e^+e^-$. This process may drive relativistic jets associated with GRB explosions. We calculate the efficiency of energy deposition by neutrinos. Our calculation is fully relativistic and based on a geodesic-tracing method. We find that the efficiency of neutrino heating is a well-defined functi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
232
1
11

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(247 citation statements)
references
References 13 publications
3
232
1
11
Order By: Relevance
“…It is interesting to contrast our results with Zalamea &Belobodorov (2011) andBirkl et al (2007). These authors found that the neutrino-antineutrino annihilation rate above the disk was greatly enhanced by the inclusion of general relativistic effects while we find that the influence of neutrinos on nucleosynthetic outcomes is decreased when general relativistic effects on emitted neutrinos are considered.…”
Section: Resultscontrasting
confidence: 56%
See 2 more Smart Citations
“…It is interesting to contrast our results with Zalamea &Belobodorov (2011) andBirkl et al (2007). These authors found that the neutrino-antineutrino annihilation rate above the disk was greatly enhanced by the inclusion of general relativistic effects while we find that the influence of neutrinos on nucleosynthetic outcomes is decreased when general relativistic effects on emitted neutrinos are considered.…”
Section: Resultscontrasting
confidence: 56%
“…Null geodesics for neutrinos emitted from accretion disks have been studied for the purposes of determining neutrino and antineutrino annihilation rates that may be relevant as an energy deposition mechanism for gamma ray bursts, e.g., Zalamea &Belobodorov (2011) andBirkl et al (2007). The typical method is to follow the null geodesics starting from the observer and ending at the neutrino surface.…”
Section: Neutrino Trajectoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…This corresponds to E=62 f r (0.67) M ☉ c 2 ≈6.7×10 54 erg, which is four orders of magnitude more than the observed energy release. Methods of tapping energy from the merged BH include neutrino-driven disks (Zalamea & Beloborodov 2011) and the Blandford-Znajek (BZ) process (Blandford & Znajek 1977;see however Lyutikov 2016).…”
Section: Radiation From a Stellar Mass Bh Mergermentioning
confidence: 99%
“…In astrophysics, "magnetars" are usually identified with objects like Soft Gamma-ray Repeaters (SGR) and Anomalous X-ray Pulsars (AXP) [4]. Recent simulations of core-collapse supernovae [5][6][7] and the formation of accretion discs at the merger of compact objects in a close binary system [8,9] demonstrate that the magnetic field strength could reach the value of B ∼ 10 15 Gauss.…”
Section: Introductionmentioning
confidence: 99%